2022
DOI: 10.3390/cancers14092077
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pancreatic Cancer with Patient-Derived Organoids Integrating Cancer-Associated Fibroblasts

Abstract: Pancreatic cancer is a devastating disease and is highly resistant to anticancer drugs because of its complex microenvironment. Cancer-associated fibroblasts (CAFs) are an important source of extracellular matrix (ECM) components, which alter the physical and chemical properties of pancreatic tissue, thus impairing effective intratumoral drug delivery and resulting in resistance to conventional chemotherapy. The objective of this study was to develop a new cancer organoid model, including a fibrous tumor micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To overcome this limitation, researchers have attempted to incorporate stromal elements in their organoid models. 5 In pancreatic cancer, a coculture model using PDOs and CAFs has been attempted, 6,7 and our group demonstrated that the CAF-integrated pancreatic cancer organoid model could better represent the patient's tumor. 7 These attempts all aim to create a better ex vivo cancer model for precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, researchers have attempted to incorporate stromal elements in their organoid models. 5 In pancreatic cancer, a coculture model using PDOs and CAFs has been attempted, 6,7 and our group demonstrated that the CAF-integrated pancreatic cancer organoid model could better represent the patient's tumor. 7 These attempts all aim to create a better ex vivo cancer model for precision medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study regarding a CAF-integrated PaC organoid model supports that deposited collagen I in the extracellular matrix counteracts the chemotherapeutic effect by blocking drug transport. 34 It is cost-effective and time-saving to use PaC cell lines, serving tumorigenic exploration and therapeutic evaluation in vitro . Yet, there is still a real gap when considering clinical customization.…”
Section: Discussionmentioning
confidence: 99%
“…The organoid model of pancreatic cancer histologically resembles human pancreatic cancer [ 221 ] with identification of pathways involved in oncology therapy [ 222 ]. Moreover, pancreas organoids were used to study diabetes and other metabolic disorders [ 223 , 224 ].…”
Section: Organoids Modeling Several Diseasesmentioning
confidence: 99%